High Purity GaAs Nanowires Free of Planar Defects: Growth and Characterization - Joyce, H; Gao, Q; Tan, H; Jagadish, C; Kim, Y; Fickenscher, M; Perera, S; Hoang, T; Smith, L; Jackson, H; Yarrison-Rice, J; Zhang, X; et al. (2008)
We investigate how to tailor the structural, crystallographic and optical properties of GaAs nanowires. Nanowires were grown by Au nanoparticle-catalyzed metalorganic chemical vapor deposition. A high arsine flow rate, that is, a high ratio of group V to group III precursors, imparts significant advantages. It dramatically reduces planar crystallographic defects and reduces intrinsic carbon dopant incorporation. Increasing V/III ratio further, however, instigates nanowire kinking and increases nanowire tapering. By choosing an intermediate V/III ratio we achieve uniform, vertically aligned GaAs nanowires, free of planar crystallographic defects, with excellent optical properties and high purity. These findings will greatly assist the development of future GaAs nanowire-based electronic and optoelectronic devices, and are expected to be more broadly relevant to the rational synthesis of other III-V nanowires. © 2008 WILEY-VCH Verlag GmbH and Co. KGaA.